Revolutionizing Learning: The Impact of Artificial Intelligence on Islamic Education and the Wave of Transformation - Zaharah Zaharah; Abdul Basyit; Muh Turizal Husein; Achmad Fauzi; Zainal Arif; Ibnu Sina (STAI Hubbulwathan Duri, 2024)
This study investigates the role of Artificial Intelligence (AI) as a tool to enhance learning practices, particularly in Islamic Religious Education. It examines AI’s potential to transform education while emphasizing the continued importance of teachers and human facilitators in the learning process. A descriptive quantitative approach was employed. Data collection was conducted using questionnaires distributed through Google Forms and supplemented with interviews. Respondents included students who provided insights into their experiences with AI in education. Findings indicate that AI technology has significant potential to improve the quality of learning and educational outcomes. Students reported that AI tools enhance their learning experiences, offering personalized and targeted assistance that complements traditional teaching methods. Despite its benefits, AI is viewed not as a replacement for educators but as a partner in achieving specific educational goals. The study highlights the transformative impact of AI on education, particularly in Islamic Religious Education, by facilitating better engagement and improved learning results. However, it underscores the indispensable role of educators in guiding and contextualizing learning to ensure alignment with educational values and goals. AI technology is a valuable tool for enhancing education but should be integrated thoughtfully to complement, not replace, the role of teachers. Its potential lies in supporting targeted and effective learning outcomes while maintaining human-centered educational practices. Further research is needed to explore AI’s long-term impacts and its application across diverse educational contexts.